The Bateman-type variational formalism for an acoustically-driven drop - Timokha, A.N. (Доповіді НАН України, 2023)
By employing the Clebsch potentials, the Bateman-type variational formulation for a drop levitating in an acoustic field is proposed when both fluids, liquid drop and external ullage gas, are barotropic, inviscid, compressible and admit rotational flows.